Perancangan Superstructure Jembatan Kereta Api Bentang 100 Meter Tipe Rangka Baja - Erlangga, Aditya Wahyu; Atmaja, Dadang Sanjaya; Dewi, Puspita (Indonesian Railway Journal, 2017)
This study discusses long bridge superstructure planning. The reference used for the  design  of  the bridge is the Regulation of the Minister of Transportation No. 60  of  2012  on  Technical  Requirements of Railways, AREMA and the rules of the European Union. The loading of the superstructure of the railway bridge includes dead load, live load, shock  load, horizontal load,  and  wind load. This bridge profile needs analysis using the influence line  method  with  SAP  2000 application. The result of superstructure analysis of 100 meter railway bridge  type  of  lower  truss frame shows that the size for structure profile,  stringer,  and  cross girder  must  be specially  designed  by utilizing SM400 type steel plate with welding. From the analysis result,  the  working  force  of stringer is 1618,74 kN with a deflection of 11,58 mm; Force on a transverse girder of 2348.16 kN; Upperchord of 6340.45 kN; Lower Frame (Lowerchord) of 7441.33 kN; And members in  the amount of 5599.48 kN. Of the styles are  designed  profiles  as follows: 1 UFLG 105 x 2.5;  2WEB  80 x 2.5; 1 UFLG 80 x 2.5 for lowerchord, 1 UFLG 105 x 3.6; 2WEB 80 x 2.5; 1 UFLG 80 x 3.6 for  upperchord  and  WF 72X x 80 x 2 x 2 For diagonal member.